Pengaruh Layanan Informasi Terhadap Peningkatan Pemahaman Siswa Kelas VIII Akan Bahaya Seks Bebas Di SMP Negeri 1 Tigabinanga - Dora Endang Lestari Surbakti (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2024)
This research aims to determine the influence of information services on increasing class VIII students' understanding of the dangers of free sex at SMP Negeri 1 Tigabinanga. The population in this study was 257 class VIII students, the sample in this study was 65 people. The sampling technique uses proportionate stratified random sampling technique. This research is a quasi-experimental research using a one group pre-test and post-test design. The data collection technique was a questionnaire regarding the understanding of the dangers of casual sex consisting of 40 items with a reliability level of 0.925. Data analysis used the T-test and analysis prerequisite tests, namely normality and homogeneity tests. This is proven from the results of the pre-test and post-test that have been carried out, the t-count is 4.201, then compared with the t-table of 1.670 because t-count > t-table, then Ho is rejected and Ha is accepted. This means that there is a significant increase in the score of understanding about the dangers of free sex (pre-test) or before providing information services (post-test) or after providing information services to class VIII students at SMP Negeri 1 Tigabinanga.